The Impact Of Disclosing Environmental Sustainability Practices On Improving Investor Decisions: An Analytical Study Of Industrial Companies In Babylon - Ahmed Kadhim Idan (Universitas Indonesia Membangun (Inaba), 2025)
This research aims to assess the level of disclosure regarding the dimensions of sustainable development (economic, social, and environmental) in companies, and to demonstrate the impact of this disclosure on investment decisions. The research stems from the fact that sustainable development has become a global imperative requiring transparency, especially in light of rapid industrial growth and its impact on these three dimensions. The research employed a descriptive-analytical approach, using data collected from a sample of companies in Babylon Governorate (N=80). The descriptive statistics revealed a general consensus among the sample regarding the importance of all study variables, with the averages for the four dimensions exceeding the hypothetical mean (3). Furthermore, opinions on investment decisions were characterized by a high degree of homogeneity. The main findings revealed a disparity in the perceived importance of the dimensions; the economic and social development dimensions recorded the highest averages, indicating that companies focus on disclosures with direct impact. In contrast, the environmental development dimension ranked lowest, indicating a relative weakness in its integration within the disclosure process that influences investment decisions. The research concluded that it is necessary to enhance environmental disclosure to ensure balance across the dimensions of sustainable development, standardize social disclosure criteria, and raise awareness among management and investors to enable them to use sustainability information more effectively in investment decision-making.